Strengthening Firm Performance Through Corporate Governance, Intellectual Capital and Financial Policy - Saifi, Muhammad; Hidayat, Kadarisman; Setyono, Langgeng; Sandi, Kemal; Kurnia, Lusi; Aina, Asri Nur (International Journal of Artificial Intelligence Research, 2023)
This study aims to examine the effect of corporate governance, intellectual capital and financial policy on firm performance conducted on 14 pharmaceutical companies listed on the Indonesian stock exchange. The data obtained was processed using warp pls software 7.0. The results of the study indicate that corporate governance has no significant positive effect on financial policy and firm performance. Meanwhile, intellectual capital has a negative and significant effect on financial policy and a significant positive effect on firm performance. Next, financial policy has a significant positive effect on firm performance.